2007
DOI: 10.1111/j.1937-5956.2007.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Item‐Level RFID in the Retail Supply Chain

Abstract: Analyzing the proliferation of item‐level RFID, recent studies have identified the cost sharing of the technology as a gating issue. Various qualitative studies have predicted that conflict will arise, in particular in decentralized supply chains, from the fact that the benefits and the costs resulting from item‐level RFID are not symmetrically distributed among supply chain partners. To contribute to a better understanding of this situation, we consider a supply chain with one manufacturer and one retailer. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(124 citation statements)
references
References 8 publications
4
120
0
Order By: Relevance
“…In a total supply chain's perspective, one can expect more speedy diffusion in total network due to significant decreases of suppliers' threshold values for the adoption. This result corresponds with Gaukler et al [13] such that in the absence of mandating entities, there exists a unique optimal way of sharing the cost of RFID tags between a supplier and a buyer. They also found that sharing the its tag cost is optimal in the sense that the total supply chain profits are maximized.…”
Section: Cost Shari Ng Wi Th Partnerssupporting
confidence: 82%
See 1 more Smart Citation
“…In a total supply chain's perspective, one can expect more speedy diffusion in total network due to significant decreases of suppliers' threshold values for the adoption. This result corresponds with Gaukler et al [13] such that in the absence of mandating entities, there exists a unique optimal way of sharing the cost of RFID tags between a supplier and a buyer. They also found that sharing the its tag cost is optimal in the sense that the total supply chain profits are maximized.…”
Section: Cost Shari Ng Wi Th Partnerssupporting
confidence: 82%
“…Under these cost issues, several literature has already studied about the optimal policies for RFID investment. Gaukler et al [13] show that in the absence of mandating entities, there exists a unique optimal way of sharing the cost of RFID tags between a manufacturer and a retailer. Sharing the tag costs is optimal in the sense that the total supply chain profits are maximized.…”
Section: Cost Shari Ng Wi Th Partnersmentioning
confidence: 99%
“…There are two main streams of literature dealing with the inventory inaccuracy problem. One stream has focused on optimal decision making when subject to inventory inaccuracy [1,11,12,21]. Specifically, these studies have dealt with the inventory errors from different sources, such as temporary shrinkage [22,23], transaction errors [24], and misplaced inventory [25,26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With RFID implementation, accurate and timely information about inventory errors can be transferred to the supplier; meanwhile, the retailer can benefit from the reduction of inventory errors. Since both the retailer and the supplier are direct beneficiaries through RFID implementation, it is reasonable to adopt RFID technology along the supply chain [11].…”
Section: Decision Policies Of the Supply Chain With Rfid Implementationmentioning
confidence: 99%
See 1 more Smart Citation